The role of exogenous lipids in starch and protein mediated sponge cake structure setting during baking. (November 2020) - Pycarelle, Sarah C.; Brijs, Kristof; Delcour, Jan A.
Graphical abstract: Highlights: Starch gelatinizes and protein polymerizes simultaneously during sponge cake baking. Use of exogenous lipids induces earlier extensive protein polymerization. The sponge cake matrix further stiffens during the isothermal phase of baking. Use of exogenous lipids leads to higher sponge cake matrix rigidity during baking. TD 1 H NMR is a potent tool to in situ study transitions during (sponge) cake making. Abstract: While it is well established that using exogenous lipids (ELs) such as monoacylglycerols and polyglycerolesters of fatty acids improves gas cell incorporation and stability in sponge cake batter (SCB) and allows producing sponge cakes (SCs) with very high volume, fine grained crumb and soft texture, their impact on starch gelatinization and protein polymerization remained unknown. Here, differential scanning calorimetry and size-exclusion high performance liquid chromatography were performed on SC(B) samples prepared with or without ELs. Starch gelatinization and protein denaturation and polymerization started at temperatures exceeding 67 °C and mostly occurred up to a temperature of 96 °C. During further isothermal treatment at 96 °C the rigidity of the cake matrix (for which temperature-controlled time domain 1 H NMR T2 relaxation times are a predictor) further increased mainly because of protein polymerization. While the temperature range of starch crystal melting was not affected by the use of ELs, protein polymerized more intensively in an 88 to 94 °C temperature range when SCB contained ELs. The more intense protein polymerization and the high water binding capacity of ELs presumably made the cake matrix more rigid at that point in time. The present results allow concluding that ELs not only impact air-liquid interface stability but also cake structure setting. Hence, both aspects most likely contribute to the superior quality of SCs containing ELs.